2011
DOI: 10.1177/2151458511426874
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of Current Management of Distal Radius Fractures in the Elderly Individuals

Abstract: Diatal radius fractures (DRFs) are typical fractures of relatively fit persons with osteoporotic bone who remain active into older age. Traditionally, DRFs in older patients have been treated with closed reduction and cast immobilization. Considering the increasing life expectancy of the elderly population, appropriate management of these fractures is of growing importance. Decision making for surgical or nonsurgical approach to osteoporotic DRFs is difficult. These decisions are often made based on the data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 44 publications
1
31
1
1
Order By: Relevance
“…Multiple linear regression (MLR) models were adopted for multivariate analysis of the DASH scores to identify the significant predictor variables. From the literature, we found that age, sex, ethnicity, type of fractures, clinicians involved, type of anaesthetic techniques and POP used affected the outcome of DRF. Therefore, we took those variables into consideration during developing MLR models.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple linear regression (MLR) models were adopted for multivariate analysis of the DASH scores to identify the significant predictor variables. From the literature, we found that age, sex, ethnicity, type of fractures, clinicians involved, type of anaesthetic techniques and POP used affected the outcome of DRF. Therefore, we took those variables into consideration during developing MLR models.…”
Section: Methodsmentioning
confidence: 99%
“…The introduction of the fixed angle locking-plate allowed for rigid stabilizer without additional intervention or bone graft. 18 This treatment type has shown positive outcomes in both the twenty to forty year old age groups and especially in the greater than sixty year old age group. 19 …”
Section: Discussionmentioning
confidence: 99%
“…Subjective and composite scores in this study agree with previous studies. 27 Some of the differences between the groups could be attributed to the higher ratio of AO/OTA type C fractures in the younger age group. However, the results of this study can be supported by biomechanical research, which demonstrated that the VLP device was efficient in the restoration of the normal axial force alignment without the reliance on screw engagement into the bone due to the nature of the screws, which mediate better locking mechanism into osteoporotic bone.…”
Section: Discussionmentioning
confidence: 99%
“…23 For unstable distal radial fractures, closed reduction has been reported to compromise functional return and result in malunion in up to 50%. 24,21,25 Treatment options include percutaneous wiring, reported as ineffective in osteoporotic bone, 26,27 dorsal plate fixation, which can lead to attrition ruptures of extensor tendons, 28 and external fixation, which carries the risk of pin tract infection and wrist stiffness. 29 One option for treating these complex fractures is by open reduction and internal fixation.…”
Section: Discussionmentioning
confidence: 99%